(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, at the new stage of the development of the society, the objective solution of the problems related to the issues of national development was widely considered not only as an important principle of the state policy, but also it was revealed from a socio-philosophical point of view that it is necessary to take into account the factors that show the effectiveness of the implemented reforms. Socio-philosophical views such as "national development", "upliftment of society", "transformation of society", "process of modernization of public administration" and at the same time "colsolidation of society" have been systematically studied.